دراسة وتحليل معامل الإرسال والانعكاس لبنية تجزيئية أحادية البعد متوضعة في وسط له معامل انكسار مختلف باستخدام طريقة الفروق المحدودة في المجال الزمني (FDTD) - صالح السموءل; زيد علي; اسعد محمد (Latakia University Journal -Engineering Sciences Series, 2018)
Fractal geometry is one of the most prominent branches of modern applied mathematics. It has developed and developed in recent years as a result of the failure of Euclidean geometry to deal with many natural and scientific phenomena. Where the fractal structure is characterized by a self-similarity feature and a unique combination of gaps that results in the emergence of pass band within prevent band . So we can use them in microwave and optical applications instead of periodic structures that needed to perform defect within their structure to get the pass band. Establishment of a software environment based on the finite difference time domain method (FDTD Finite difference time domain), was done in this research for studying and analyzing the one dimension fractal structure in order to accurately characterize the fractal one-dimension structure based on electromagnetic field parameters, and simulation of the propagation of electromagnetic waves within the fractal one-dimensional structure located in free space ,and calculate transmission and reflection coefficient, and study of the effect of fractal factors such as stage of growth, fractal dimension and the type of material studied on the transmission and reflection coefficient. In order to obtain a high selective filter تعد الهندسة التجزيئية أحد أبرز فروع الرياضيات التطبيقية الحديثة, وقد ظهرت وتطورت خلال السنوات الأخيرة نتيجة قصور الهندسة الإقليدية عن معالجة الكثير من الظواهر الطبيعية والعلمية, حيث تتميز البنى التجزئيية بخاصية التشابه الذاتي وبتركيبة فريدة تحوي فجوات ينتج عنها ظهور حزم تمرير ضمن حزم المنع الترددية, وبالتالي يمكننا استخدامها في التطبيقات الميكروية والضوئية بدلاً عن البنى الدورية التي كانت تحتاج إلى إحداث خلل ضمن بنيتها للحصول على حزم التمرير. تم في هذه الدراسة بناء بيئة برمجية لدراسة وتحليل البنية التجزيئية أحادية البعد بالاعتماد على طريقة الفروق المحدودة في المجال الزمني (FDTD Finite difference time domain method ), وذلك بهدف توصيف البنية التجزيئية أحادية البعد بشكل دقيق اعتمادا على معاملات الحقل الكهربائي والمغناطيسي, ومحاكاة انتشار الأمواج الكهرومغناطيسية ضمن البنية التجزيئية أحادية البعد المتوضعة في الفراغ الحر, وحساب معامل الإرسال والانعكاس ودراسة تأثير معاملات الجسم التجزيئي مثل درجة التجزيء, والبعد التجزيئي ونوع المادة المدروسة على معامل الإرسال والانعكاس, بهدف الحصول على مرشح عالي الانتقائي